2013
DOI: 10.6061/clinics/2013(07)10
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of dental caries is associated with atherosclerosis

Abstract: OBJECTIVE:Previous studies have suggested that marginal periodontitis is a risk factor for developing atherosclerosis. The objective of this study was to determine whether caries may also be associated with atherosclerosis.METHODS:The computed tomography data sets of 292 consecutive patients, 137 women and 155 men with a mean age of 54.1±17.3 years, were analyzed. Caries were quantified based on the number of decayed surfaces of all the teeth, and periodontitis was quantified on the basis of the horizontal bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 40 publications
2
30
0
2
Order By: Relevance
“…Periodontal disease is associated with a highly elevated risk of all-cause mortality (DeStefano et al 1993), and it is a risk factor for cardiovascular diseases, respiratory infections, cancer, diabetes mellitus, renal disease, and numerous other poor health outcomes (Li et al 2000;Williams et al 2008;Ylostalo et al 2006). Dental caries is associated with such adverse health conditions as cardiovascular disease, asthma, liver disease, and poor growth (Acs et al 1999;Glodny et al 2013;Johnston and Vieira 2014). Periodontal disease and dental caries may be causally related to diseases such as cardiovascular disease, cancer, and respiratory infections by affecting systemic inflammatory cytokine levels and via the spread of infectious pathogens from the oral cavity to other parts of the body (Beck and Offenbacher 2005;Joshipura et al 2006;Lombardo Bedran et al 2013;Loos 2005;Meyer et al 2008;Paju and Scannapieco 2007;Watts et al 2008).…”
Section: Advances In Our Understanding Of Lesion-formation Processesmentioning
confidence: 97%
“…Periodontal disease is associated with a highly elevated risk of all-cause mortality (DeStefano et al 1993), and it is a risk factor for cardiovascular diseases, respiratory infections, cancer, diabetes mellitus, renal disease, and numerous other poor health outcomes (Li et al 2000;Williams et al 2008;Ylostalo et al 2006). Dental caries is associated with such adverse health conditions as cardiovascular disease, asthma, liver disease, and poor growth (Acs et al 1999;Glodny et al 2013;Johnston and Vieira 2014). Periodontal disease and dental caries may be causally related to diseases such as cardiovascular disease, cancer, and respiratory infections by affecting systemic inflammatory cytokine levels and via the spread of infectious pathogens from the oral cavity to other parts of the body (Beck and Offenbacher 2005;Joshipura et al 2006;Lombardo Bedran et al 2013;Loos 2005;Meyer et al 2008;Paju and Scannapieco 2007;Watts et al 2008).…”
Section: Advances In Our Understanding Of Lesion-formation Processesmentioning
confidence: 97%
“…One of them, however, did not show significance following multivariable analysis (Glodny et al . ). The quality assessment showed a lack of high‐quality longitudinal studies investigating the association between AP and CVD.…”
Section: Reviewmentioning
confidence: 97%
“…, Glodny et al . ). Periodontitis is a known risk factor for CVD and is a potential confounder that may be responsible for the positive association between AP and CVD in some studies, as it was not controlled (Oikarinen et al .…”
Section: Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…9 An association between periodontal disease and dyslipidemia, 10 diabetes, 11 and cardiovascular disease 12 has been suggested. 17 Several studies have shown that dental caries and associated bacteria may elicit a potent T helper (T h ) 1 immune response in peripheral blood mononuclear cells and promote CD8 + T cell responses, 18 and T h 2 and T h 17 cell responses were shown to be positively associated with increased risk of insulin resistance. 13,14 Moreover, dental caries is associated with obesity and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%